The Free Nutritional Meal Program (MBG) in Education: Analysis of Problems and Challenges of Implementation - Bulan Febriyanti; Deny Aprilian; Ghinaa Syifaa Ariibah (Horizons : Journal of Education and Social Humaniora, 2026)
The Free Nutritious Meal Program (MBG) is a national policy aimed at improving the nutritional status of students. However, its implementation at the school level faces significant operational obstacles. This study aims to identify and analyze the problems and challenges of implementing MBG in schools. The method used was a systematic literature review of scientific journals, research institute reports, and national media coverage for the 2025-2026 period. The study identified five main problems: (1) the MBG schedule being out of sync with learning hours, (2) limited school facilities and infrastructure, (3) the increased workload of non-pedagogical teachers, (4) the menu not matching the diverse needs of students, and (5) the school's unpreparedness in managing distribution and quality standardization. Each problem is explained based on its form, cause, and implementation challenges. The study concludes that the success of MBG depends heavily on the readiness of schools as the spearhead of implementation. Therefore, improvements in governance, provision of supporting facilities, and a clear division of roles between teachers and operational staff are needed.